1980
DOI: 10.1007/bf01965965
|View full text |Cite
|
Sign up to set email alerts
|

Spore germination inHebeloma stimulated by living plant roots

Abstract: Basidiospores from 14 strains of Hebeloma (Agaricales) representing 5 groups of mycorrhiza-forming species were tested for germination on a nutrient agar medium. Germination occurred in 13 strains but never exceeded 0.1%. A 10fold increase or more in germination percentage was obtained in 4 out of 7 tested spore collections only by placing the growing root of a pine seedling among the spores on the agar medium.Basidiospores of mycorrhiza-forming Homobasidiomycetes generally do not germinate on ordinary agar me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In fact, spores of many ECMF species may remain dormant until germination is triggered by the presence of a suitable host plant, such as an establishing seedling [73], [76], [77]. This indirect influence of ectomycorrhizal shrubs on soils not vegetated by ectomycorrhizal hosts appears to occur at the scale of our sampling sites, but does not seem to extend further, such as into the glacial moraine.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, spores of many ECMF species may remain dormant until germination is triggered by the presence of a suitable host plant, such as an establishing seedling [73], [76], [77]. This indirect influence of ectomycorrhizal shrubs on soils not vegetated by ectomycorrhizal hosts appears to occur at the scale of our sampling sites, but does not seem to extend further, such as into the glacial moraine.…”
Section: Discussionmentioning
confidence: 92%
“…Four weeks after inoculation 34 and 31 % basidiospores of S. luteus and S. granulatus had germinated, respectively, while 46 % R. luteolus spores germinated under the same conditions. DISCUSSION Fries & Birraux (1980) and Birraux & Fries (1981) showed that when pine roots were placed on plates of nutrient agar seeded with basidiospores of the ectomycorrhizal fungi Hebeloma spp. and Thelephora terrestris Ehrh.…”
Section: Stimulation Of Suillus Speciesmentioning
confidence: 99%
“…Although the rhizosphere is considerably richer in energy sources than is soil, the much longer generation time of bacteria in the rhizosphere than on laboratory media (Bowen & Rovira, 1976) indicates that it is certainly not an optimal medium. Fries & Birraux (1980) observed that certain young myeelia from germinated spores in synthetic media died for unknown reasons. However, the percentage germination obtained in these studies guarantees a good level of infection even if some germ tubes die off before they grow into infective mycelium.…”
Section: Stimulation Of Suillus Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although host roots and root exudates improve EMF spore germination (Bowen, 1994, and references therein), the extent of the host effect on spore germination varies considerably (Fries, 1987). For example, pine ( Pinus radiata ) seedlings enhanced spore germination by up to 34 and 69% in species of Suillus and Rhizopogon , respectively (Theodorou & Bowen, 1987), whereas germination was as low as 1% in Hebeloma species (Fries & Birraux, 1980). To date, the causes of such variation in EMF spore germination are poorly understood.…”
Section: Introductionmentioning
confidence: 99%